Implementasi Akuntansi Syariah dalam Meningkatkan Kredibilitas dan Transparansi Laporan Keuangan Perusahaan - Widia Agus; Andi Muhammad Nur Wahyuddin. AS; Ariel Kurniawan; Masyhuri Masyhuri (Indo Publishing, 2026)
This research discusses the role of Islamic accounting implementation in enhancing the credibility and transparency of corporate financial statements. The study applies a descriptive qualitative method through a literature review approach by collecting information from books, scientific journals, and other academic references related to Islamic accounting practices. The findings reveal that Islamic accounting principles, including honesty, accountability, fairness, and transparency, contribute significantly to improving the quality of financial reporting. The application of these principles encourages companies to provide financial information accurately, openly, and responsibly, which helps reduce the possibility of fraud and manipulation in financial statements. Furthermore, transparent and reliable financial reporting can strengthen investor confidence and improve the company’s reputation among stakeholders. Islamic accounting also supports the development of better corporate governance because it emphasizes ethical values and responsibility in business activities. Therefore, the implementation of Islamic accounting can be considered an important approach in creating trustworthy financial statements and maintaining sustainable business practices in accordance with Islamic values.